'True Democratic Sympathy': Charles Stubbs, Christian Socialism, and English Labour, 1863–1912. Issue 1 (April 2018) - Chase, Malcolm
Abstract : Charles Stubbs (1845–1912) was the most senior Anglican clergyman to engage supportively with the labour movement in the decades before the Great War. From a curacy in Sheffield during the 1860s he rose to become first Dean of Ely (from 1894) and then Bishop of Truro (from 1906 until his death). The titles of some of his many books give a good flavour of their author: Village Politics: Addresses and Sermons on the Labour Question; The Land and the Labourers (five editions, 1885–1904); Christ and Economics; A Creed for Christian Socialists . An early member of the Guild of St Matthew, a small but influential Christian socialist society founded in 1877 'to justify God to the people', Stubbs was a powerful influence on an important but neglected facet of Christian socialism, one that was 'Broad Church' rather than Anglo-Catholic. He was also widely admired in progressive liberal and trade unionist circles for his practical involvement in campaigns in support of land reform, rural renewal, and agricultural labour. This article analyses his thinking about the 'social witness' of Christianity, arguing it was an important bridge between the theology of the mid-Victorian socialist F.D. Maurice and post-First World War Christian socialism.